Festejo do Divino Espírito Santo na comunidade quilombola malhadinha - Cézar, Gederson Moreira (Universidade Federal do Tocantins, 2023)
This article aims to report on the festive experiences of the feast of the Divine Holy Spirit in the Quilombola Community Malhadinha Brejinho de Nazareth. In Brazil, to a great difficulty of finding records, of the festivities of the black people, being for that, one of these reasons that led me to the construction of this article, as a way of breaking this paradigm. This work also aims to show the readers the construction of this feast, and the meaning of the religiousness of each resident devotee or not, in general terms, is aimed at understanding the feast of the Divine in Quilombo de Malhadinha.